Bioprocess analysis and phase equilibria for the removal of Eicosane from palm oil using sub critical solvent - Che Norsuhada Che Hussin (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
This project is mainly about the extaction or removal processof the eicosane from palm oil by using sub critical solvent. The method of removal process can be divided into two, which are atmospheric pressure extraction and high pressure extraction. In this project, the experimental work has been conducted in atmospheric pressure condition. The methods that have been used are simple distillation and water bath extraction. Both methods are involving the use of subcritical solvent which is hexane. The temperature was manipulated to determine the effect of temperature on the extraction method. The palm oil extract were analysed using fourier transform infrared spectroscopy (FTIR) and diffrential scanning calorimeter (DSC) to determine the compositions of the palm oil that has been extracted.